Interaksi Geminivirus pada Kejadian Inokulasi Ganda - Sri Hendrastuti Hidayat; Rina Rachmawati; Puji Lestari; Noor Aidawati (Universitas Gadjah Mada, 2005)
Incidence of geminivirus infection has been caused severe losses on various economically important crops. This losses may cause by single infection or mix infection of several strain of geminiviruses. In this experiment we used two strain of geminiviruses, geminivirus infecting chillipepper from Segunung, West Java and geminivirus infecting tomato from Lembang, West Java (GVToL), to study the effect of geminivirus mix infection on the symptom expression and the capability of each strain to multiply in the host cell. Coefficient of dissimilarity between this two strain of geminiviruses is 7.5. When the two strain of geminiviruses was inoculated together to tomato plants by insect vector; Bemisia tabaci, the symptoms on infected plants is slightly different but less severe than those on plants inoculated with each strain separately. Detection with polymerase chain reaction (PCR) followed by restriction enzyme digest of PCR product revealed that GVToL multiply better in the infected host cell.